Unshrouding effects on demand for a costly add-on: Evidence from bank overdrafts in Turkey - Sule Alan; Mehmet Cemalcilar; Dean Karlan; Jonathan Zinman (Yale University, Economic Growth Center, 2015)
Models of shrouding predict that firms lack incentives to compete on add-on prices. Working with a large Turkish bank to test SMS direct marketing promotions to 108,000 existing checking account holders, we find that messages promoting a large discount on the overdraft interest rate reduce overdraft usage. In contrast, messages that mention overdraft availability without mentioning price increase usage. Neither change persists long after messages stop, suggesting that induced overdrafting is not habit-forming. Our results are consistent with a model of limited memory and attention.
Keywords: D12; D14; G2; 330; contingent charges; limited attention; salience; advertising; habit formation; consumer banking; retail banking; deposit accounts